Proton Radiation Hardness of Perovskite Solar Cells Utilizing a Mesoporous Carbon Electrode - Declan Hughes (Energy Technology, 2021)
When designing spacefaring vehicles and orbital instrumentation, the onboard systems such as microelectronics and solar cells require shielding to protect them from degradation brought on by collisions with high‐energy particles. Perovskite solar cells (PSCs) have been shown to be much more radiation stable than Si and GaAs devices, while also providing the ability to be fabricated on flexible substrates. However, even PSCs have their limits, with higher fluences being a cause of degradation. Herein, a novel solution utilizing a screen‐printed, mesoporous carbon electrode to act bi‐functionally as an encapsulate and the electrode is presented. It is demonstrated that the carbon electrode PSCs can withstand proton irradiation up to 1 × 1015 protons cm−2 at 150 KeV with negligible losses (<0.07%) in power conversion efficiency. The 12 μm thick electrode acts as efficient shielding for the perovskite embedded in the mesoporous TiO2. Through Raman and photoluminescence spectroscopy, results suggest that the structural properties of the perovskite and carbon remain intact. Simulations of the device structure show that superior radiation protection comes in conjunction with good device performance. This work highlights the potential of using a carbon electrode for future space electronics which is not limited to only solar cells.